Micromixers : fundamentals, design and fabrication - Nguyen, Nam-Trung, 1970- (Micro & nano technologies., 2011)
The ability to mix minute quantities of fluids is critical in a range of recent and emerging techniques in engineering, chemistry and life sciences, with applications as diverse as inkjet printing, pharmaceutical manufacturing, specialty and hazardous chemical manufacturing, DNA analysis and disease diagnosis. The multidiscliplinary nature of this field - intersecting engineering, physics, chemistry, biology, microtechnology and biotechnology - means that the community of engineers and scientists now engaged in developing microfluidic devices has entered the field from a variety of different backgrounds. The strength of this book is that it enables this very diverse community to gain a thorough grounding in the fundamentals and practical aspects of micromixers in order to deploy them effectively in a variety of contexts. 'Micromixers' is uniquely comprehensive, in that it deals not only with the problems that are directly related to fluidics as a discipline (aspects such as mass transport, molecular diffusion, electrokinetic phenomena, flow instabilities, etc) but also with the practical issues of fabricating micomixers and building them into microsystems and lab-on-chip assemblies. With practical applications to the design of systems vital in modern communications, medicine and industry this book has already established itself as a key reference in an emerging and important field. The second edition includes coverage of a broader range of fabrication techniques, additional examples of fully realized devices for each type of micromixer and a substantially extended section on industrial applications, including recent and emerging applications. Introduces the design and applications of micromixers for a broad audience across chemical engineering, electronics and the life sciences, and applications as diverse as lab-on-a-chip, ink jet printing, pharmaceutical manufacturing and DNA analysis Nguyen helps engineers and scientists to unlock the potential of micromixers by explaining both the scientific (microfluidics) aspects and the engineering involved in building and using successful microscale systems and devices with micromixers.